The Development of a Novel Resilience Scorecard: What We Can Learn from Supply Chain Logistics - Sims, Harrison (Proceedings of the International Symposium of Human Factors and Ergonomics in Healthcare, 2025)
The development of more resilient healthcare systems can substantially improve patient safety by enabling providers to withstand, adapt to, and overcome unforeseen circumstances. Despite these benefits, resilience engineering remains a challenge as a quantitative measurement of resilience has yet to be proposed. While prior work has introduced qualitative resilience frameworks, this work identifies a quantitative resilience framework to measure resilience in the anesthesia delivery process. Resilience is integral to and well-studied in the supply chain logistics field, and in this study, resilience scorecards from supply chain logistics were adapted to the anesthesia domain. The proposed anesthesia resilience scorecard addresses three primary dimensions: distribution resilience, sourcing resilience, and information transmission resilience. By quantifying resilience in the anesthesia delivery system, this measurement tool enables informed innovation and demonstrates the value of adapting research findings from quantitative disciplines. Future work will focus on the validation of the proposed scorecard.